2017
DOI: 10.35609/jfbr.2017.2.2(2)
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Earnings Management in the Indonesian Stock Exchange

Abstract: Objective - The purpose of this research is to analyze the effect of growth, leverage, fixed asset turnover, profitability, firm size, firm age, industry, audit quality, and auditor independence toward earnings management. Methodology/Technique - The population of this research consist of various sectors of non-financial companies that were listed on the Indonesian Stock Exchange (IDX) between 2013 and 2015. The research uses three recent years of data and tests variables that have not been used by prior rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 11 publications
3
19
0
10
Order By: Relevance
“…This study is in line with the results of the study of (Fitri et al, 2018) and (Alexander and Hengky, 2017) that profitability has a positive and significant effect on earnings management. However, it is inversely proportional to the results of research conducted by (Wiyadi et al, 2015) and (Agustia and Suryani, 2018) that profitability has no significant effect on earnings management.…”
Section: Effect Of Profitability On Earnings Managementsupporting
confidence: 92%
See 1 more Smart Citation
“…This study is in line with the results of the study of (Fitri et al, 2018) and (Alexander and Hengky, 2017) that profitability has a positive and significant effect on earnings management. However, it is inversely proportional to the results of research conducted by (Wiyadi et al, 2015) and (Agustia and Suryani, 2018) that profitability has no significant effect on earnings management.…”
Section: Effect Of Profitability On Earnings Managementsupporting
confidence: 92%
“…When profitability is low, management will be encouraged to do earnings management because if the profitability of a company is low or experiences losses, this is in the eyes of investors is a sign that it does not make investments in the company (Mulyana et al, 2018). Research conducted by (Agustia and Suryani, 2018), (Firtri et al, 2018) shows that profitability has a significant effect on earnings management while research conducted by (Alexander and Hengky, 2017) states that profitability does not significantly influence earnings management.…”
Section: Introductionmentioning
confidence: 99%
“…Di Indonesia, terdapat beberapa penelitian yang membahas mengenai pengaruh tingkat pendanaan utang terhadap praktik manajemen laba secara persial. Alexander & Hengky (2017) membahas mengenai faktor-faktor yang mempengaruhi perusahaan melakukan manajemen laba, namun tingkat pendanaan utang tidak berpengaruh signifikan terhadap manajemen laba, yang paling berpengaruh adalah tingkat probabilitas yang diproksikan dengan Return on Assets (ROA). Di penelitian berikutnya, Astuti et al (2017) membahas mengenai pengaruh ukuran perusahaan dan leverage terhadap manajemen laba khusus untuk perusahaan perbankan di Indonesia.…”
Section: Pendahuluanunclassified
“…Previous research done by Craswell et al (1995) found that the audit quality has negative impact on earnings management. Meanwhile, Alexander and Hengky (2017), Arifin and Destriana (2018) and Florencia and Susanty (2019) showed that there is no influence of audit quality on earnings management. Jensen and Meckling (1976) found evidence that managerial ownership succeeded for reducing agency problems from managers by aligning the interests of managers with shareholders.…”
Section: Audit Qualitymentioning
confidence: 99%